Hazelnut days - Bourdier, Emmanuel, 1972- (Minedition, published by Michael Neugebauer Publishing, 2018)
It's visiting day, and Dad smells like peppermintyuck! If only he would wear that nice, breezy cologne that smells like hazelnut... So begins one boys brief weekly visit with his father in prison. Heres a man who gets angry, but beneath that peppermint surface is much to admire, if only you take the time to look. This richly imagined picture book explores the inner life of a boy who struggles to love a father who can be difficult to love at times. Though they may only have brief visits together, its clear they love each other. This story bravely explores the all-too-hidden world of incarcerated parents. Its also a beautiful testament to the power of love to bridge the walls that divide us.